PEMBERDAYAAN SUMBER DAYA ALAM BERBASIS KEARIFAN LOKAL DI WILAYAH KERJA RESORT SEMANGIT - Sekolastika Febria Ema; Kartini Kartini; Jumiati Jumiati; Robby Irsan (Universitas Lambung Mangkurat, 2022)
Semangit Resort is a management unit of Lake Sentarum National Park that has wealth and biodiversity as a supporter of conservation development, sustainable economy, and socio-cultural life of the local community. The natural resources available there are utilized by local communities to meet economic needs. People in the Semangit Resort Work Area conduct natural resource management based on local wisdom because local habits have been done since long ago and can support the sustainability of natural resources. This research aims to find out the available natural resources, the form of local wisdom in the management of natural resources, and their effect on improving the economy of the community in the Semangit Resort Work Area. The method of data collection in this study is done by doing field observations, semi-structured interviews, and documentation of community activities. The data obtained is then analyzed, assisted by the literature related to the purpose of research. The results of this study show that the available natural resources are divided into 3 sectors, namely the fisheries sector, the forest products sector, and the agricultural and plantation sectors. Most of the local wisdom carried out by the community related to the management of natural resources is proven to improve the economy of the community. This shows that natural resource management based on local wisdom can improve the economy in support of sustainable development.